2013
DOI: 10.1038/nm.3181
|View full text |Cite
|
Sign up to set email alerts
|

Fgf9 from dermal γδ T cells induces hair follicle neogenesis after wounding

Abstract: Understanding molecular mechanisms for regeneration of hair follicles provides new opportunities for developing treatments for hair loss and other skin disorders. Here we show that fibroblast growth factor 9 (Fgf9), initially secreted by γδ T cells, modulates hair follicle regeneration after wounding the skin of adult mice. Reducing Fgf9 expression decreases this wound-induced hair neogenesis (WIHN). Conversely, overexpression of Fgf9 results in a two- to threefold increase in the number of neogenic hair folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
294
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(319 citation statements)
references
References 36 publications
12
294
3
6
Order By: Relevance
“…A more recent study from Gay et al (2013) showed the role of FGF9 secretion from gd-T Figure 2. Schematic illustration of molecular mechanisms during hair follicle morphogenesis (top) and neogenesis (bottom).…”
Section: Regeneration Of Skin Appendages-hair Follicle Neogenesismentioning
confidence: 99%
“…A more recent study from Gay et al (2013) showed the role of FGF9 secretion from gd-T Figure 2. Schematic illustration of molecular mechanisms during hair follicle morphogenesis (top) and neogenesis (bottom).…”
Section: Regeneration Of Skin Appendages-hair Follicle Neogenesismentioning
confidence: 99%
“…in the dermal fibroblasts during cutaneous wound healing. Although there are slight variations of activity levels with the wounds in other references (Gay et al, 2013;Whyte et al, 2013), these results are still correlated. Endothelin-1, a target of Wnt/-catenin pathway, was also specifically increased in the fibroblasts of CXXC5 / mouse wounds.…”
Section: Co-treatment With Ptd-dbm and Vpa Accelerates Cutaneous Wounmentioning
confidence: 71%
“…From having assumed that hair follicles are only created during embryogenesis, there is some evidence that new hair follicles can be created during wound healing Gay et al, 2013), giving hope to many researchers that one might eventually nd a cure for baldness.…”
Section: Hair Folliclesmentioning
confidence: 99%
“…. Cotsarelis, G. (2013 Physiol, 211(2), 353-363 Hennings, H., Holbrook, K., Steinert, P. and Yuspa, S. (1980). Growth and differentiation of mouse epidermal cells in culture: effects of extracellular calcium.…”
mentioning
confidence: 99%